Preparing Multicultural Educators: What Works According to Practicing and Future Teachers - Laureen Fregeau (Networks: An Online Journal for Teacher Research, 2001)
I have been preparing teachers and pre-service teachers to be multicultural educators since 1990. Each year I ask my students what works best for them. My course activities and assignments evolve each year with the help of student suggestions. This article offers a theoretical framework for the assignments and activities students selected; summarizes what assignments and classroom activities students identified as most effective and enjoyable; and, shares specifics of each type of assignment.